A utilização de recursos visuais no ensino de geometria para estudantes surdos - DOURÃO, Isane Pantoja (2023)
This article aims to reflect on the teaching of mathematics for deaf students in the educational field, and from this perspective, we sought to analyze and thus demonstrate, through an intervention, ways to provide opportunities for inclusive teaching within the scope of regular education. The present study is a field and exploratory research having the analysis in a qualitative way. Thus, it could be observed that the intervention that was explained in the present work, had a strengths, since it allowed the deaf student and the other classmates, the visualization and identification of some geometric figures and their characteristics, through the concepts displayed, such as area and perimeter. Since the geocampo is just one example of what can be used by mathematics teachers in the educational field, aiming at the applicability of what is guaranteed by the legislation, and thus, providing opportunities for the construction of a inclusive school, in which there is an egalitarian concern for the learning of its students and always taking into account the differences of each student